2009
DOI: 10.3126/hn.v4i0.1825
|View full text |Cite
|
Sign up to set email alerts
|

Quasi - 3D and Full - 3D Approaches for Numerical Simulation in Axial Flow Hydraulic Turbine

Abstract: Water passes through the rows of stationary and rotating blades in the turbine space and thus the flow becomes complex. The application of computational fluid dynamics (CFD) is steadily increasing to improve design of hydraulic turbines. The numerical flow simulation in the hydraulic turbine space can either be based on potential or viscous flow theory. In both the approaches, detailed flow behavior in complete turbine space is obtained. The quasi- 3D potential flow approach is quick and simple as compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…Sahu and Gandhi [8] conclude that flow over guide vane is highly unsteady, complex, and associated with various assumptions and uncertainties. Prasad et al [9] carried out a steady-state flow simulation on an axial turbine that was experimentally tested at 3 different conditions using the k-ω model and found that the numerical values were in close agreement with the experimental values. Trivedi et al [2] carried out an unsteady numerical analysis of a high head turbine, selecting the standard k-ε and k-ω shear stress transport (SST) turbulence models.…”
Section: Introductionmentioning
confidence: 82%
“…Sahu and Gandhi [8] conclude that flow over guide vane is highly unsteady, complex, and associated with various assumptions and uncertainties. Prasad et al [9] carried out a steady-state flow simulation on an axial turbine that was experimentally tested at 3 different conditions using the k-ω model and found that the numerical values were in close agreement with the experimental values. Trivedi et al [2] carried out an unsteady numerical analysis of a high head turbine, selecting the standard k-ε and k-ω shear stress transport (SST) turbulence models.…”
Section: Introductionmentioning
confidence: 82%
“…The mass of the material is very influential on the change in potential energy present in the flow of water into mechanical energy as the rotation of the water wheel used to turn the generator to produce electrical energy (Adanta et al, 2020). Prasad et al (2009) compared the axial efficiency of flow turbines coming through experimental and CFD analysis with three different guide vane angles. Whereas Jain et al (2010) conducted a study of the performance and efficiency of a French turbine in four different operations at the propeller point by using CFD and to validate the same as evaluating the model.…”
Section: Introductionmentioning
confidence: 99%
“…The second analyzed model is k-ω SST (Shear-Stress Transport), which combines standard k-ω model near the wall and k-ε model in the outer portion of the boundary layer. It gives the accurate results for flows with adverse gradient pressure (flows with separation), therefore it is reliable for turbines [9,10]. Finally, the one-equation Spalart-Allmaras turbulent model is applied.…”
Section: Introductionmentioning
confidence: 99%